The naa40 Deletion Is Associated with Extended Chronological Lifespan and Changes in Energy and Lipid Metabolism in Fission Yeast - Çalici Z; BUSE, ÖZDEN; Tarhan Ç. (Pleiades Publishing, 2025)
Abstract: Aging is associated with various physiological and molecular changes, including epigenetic reprogramming and metabolic remodeling. N-alpha-acetyltransferase 40 (NAA40), encoded by naa40, has emerged as a key factor connecting chromatin dynamics to cellular metabolism among epigenetic regulators. NAA40 specifically acetylates the N-termini of histones H4 and H2A, thereby influencing gene expression and maintaining the metabolic balance. In mammalian systems, the depletion of NAA40 increases intracellular acetyl-CoA levels, which impacts lipid metabolism and stress response pathways. However, the overall effects of naa40 deletion in organisms are not fully understood. In this study, we examined the functional consequences of naa40 deletion in Schizosaccharomyces pombe by analyzing changes in chronological lifespan, glucose consumption, lipid metabolism, and oxidative stress. Our findings indicate that the loss of NAA40 significantly extends the lifespan, decreases glucose utilization, alters lipid distribution, and reduces lipid peroxidation. These metabolic changes are similar to the cellular adaptations observed under calorie restriction. Our results support a model in which naa40 deletion triggers chromatin remodeling and reprograms the metabolic pathways, ultimately leading cells to a quiescent-like state characterized by increased stress resistance and extended survival. These findings underscore the importance of NAA40 as a critical link between epigenetic regulation and the mechanisms that promote metabolic longevity.
Keywords: Aging; Calorie Restriction; Lipid Metabolism; NAA40; Schizosaccharomyces Pombe